Introducing the scanning air puff tonometer for biological studies - Fleury, Vincent; Al-Kilani, Alia; Boryskina, Olena P.; Cornelissen, Annemiek J. M.; Nguyen, Thi-Hanh; Unbekandt, Mathieu; Leroy, Loïc; Baffet, Georges; le Noble, Ferdinand; Sire, Olivier; Lahaye, Elodie; Burgaud, Vincent (Physical review. E, Statistical, nonlinear, and soft matter physics, 2010)
It is getting increasingly evident that physical properties such as elastoviscoplastic properties of living materials are quite important for the process of tissue development, including regulation of genetic pathways. Measuring such properties in vivo is a complicated and challenging task. In this paper, we present an instrument, a scanning air puff tonometer, which is able to map point by point the viscoelastic properties of flat or gently curved soft materials. This instrument is an improved version of the air puff tonometer used by optometrists, with important modifications. The instrument allows one to obtain a direct insight into gradients of material properties in vivo. The instrument capabilities are demonstrated on substances with known elastoviscoplastic properties and several biological objects. On the basis of the results obtained, the role of the gradients of elastoviscoplastic properties is outlined for the process of angiogenesis, limb development, bacterial colonies expansion, etc. which is important for bridging the gaps in the theory of the tissue development and highlighting new possibilities for tissue engineering, based on a clarification of the role of physical features in developing biological material.